PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM PERHITUNGAN PROFITABILITAS PRODUK PADA UD. NIAGA BAKTI - Fena Ulfa Aulia; Khairul Anam (Institut Agama Islam Negeri Madura, 2015)
The Charge imposition of factory overhead based on traditional systems often cause distorted costs. One of efforts to overcome these distortions fees is with charging the costs factory overhead by the activity based costing. The use of activity based costing can also help companies that produce many products in determining the level of profitability. Profitability indicates whether an enterprise has good prospects in the future for the company's survival. This research is a quantitative descriptive research conducted at UD NIAGA BAKTI engaged in the processing of tuna fish PETIS in Pamekasan located in the village of Konang, Subdistrict of Galis, Regency of Pamekasan. The type of data used in this research is quantitative data obtained by direct observation and Interview. This techniques of research analysis calculates and compares the products profitability of PETIS by using traditional cost systems and costing system based activity. The results of this research indicates that there are differences in the principal cost of production and profitability UD NIAGA BAKTI by using activity based costing compared Traditional Cost Systems.